Factors that Influence the Performance of Medical Record Technicians at Sibuhuan Hospital - Indah, Indah Aulia Sari; Rahmadia, Putri; Sari, Novita; Sakinah, Heny; Amelia, Robyatul Tyas; Kusmiati, Vivi (International Journal of Public Health Excellence (IJPHE), 2025)
This research aimed to determine the factors that influence the performance of technicians at Sibuhuan Regional General Hospital in 2024. This research analysed factor that influences the performances of medical records based three factors: individual factors (skill, work experience, and abilities), psychological indicators (perception, motivation, job satisfaction and role), organizational (work design, leadership, and reward). The researcher used a descriptive approach by distributing questionnaires, obtained through distributing questionnaires by distributing medical record. The number of samples obtained 5 participants. This study indicated that factor that influences the performances of medical records technicians is individual factors, including Skill (40%), Work Experience (20%), and Abilities (20%). The second factor is psychological indicators namely perception (20%), Motivation (20%), Job Satisfaction (40%) and Role (20%). The third factor is organizational indicators including Work Design (20%), Leadership (20%), and Reward (60%). At long last, it can be concluded that the factor that influence the performance of medical record technicians are dominant in the skill, job satisfaction, and rewards.